Interplay of cellular cAMP levels, σ(S) activity and oxidative stress resistance in Escherichia coli - Barth, Evelyn (Microbiology Society, 2009)
Hypochlorous acid (HOCl), the active ingredient of household bleach, functions as a powerful antimicrobial that is used not only in numerous industrial applications but also in mammalian host defence. Here we show that multicopy expression of cpdA, encoding the cAMP phosphodiesterase, leads to a dramatically increased resistance of Escherichia coli to HOCl stress as well as to the unrelated hydrogen peroxide (H(2)O(2)) stress. This general oxidative stress resistance is apparently caused by the CpdA-mediated decrease in cellular cAMP levels, which leads to the partial inactivation of the global transcriptional regulator cAMP receptor protein (CRP). Downregulation of CRP in turn causes the derepression of rpoS, encoding the alternative sigma factor σ(S), which activates the general stress response in E. coli. We found that these highly oxidative stress-resistant cells have a substantially increased capacity to combat HOCl-mediated insults and to degrade reactive oxygen species. Mutational analysis revealed that the DNA-protecting protein Dps, the catalase KatE, and the exonuclease III XthA play the predominant roles in conferring the high resistance of rpoS-overexpressing strains towards HOCl and H(2)O(2) stress. Our results demonstrate the close regulatory interplay between cellular cAMP levels, σ(S) activity and oxidative stress resistance in E. coli.